Multi-Level Marketing As a Part-Time Career Option among the Youth (A Cross-National Study of Malaysia and the Arab World) - Said Salim, Khamis Jeneby (2013)
In many years, businesses were able to connect with the consumers through marketing. However in today’s world, the consumers have become part of the businesses through multi-level marketing. In Malaysia, there is an increased competitiveness and turbulence in the labor market. The number of people getting into the job market is not equivalent to the number of jobs available. The saturation of the labour market leads to most of the people ending up with a lower salary which is not sufficient to cater for the daily needs. Multi-level marketing can be one of the ways of eliminating this tragedy through the generation of additional income that will complement the basic salary. Most of the people have been doing extensive research about the existence of multi-level marketing. However, only handful studies have really examined the willingness of the youth to undertake multi-level marketing as a part-time career option among the youth. In this research a cross-national study between Malaysia and the Arab world will be done to investigate on the willingness of the youth to undertake multi-level marketing as a part-time career option. There will be an investigation on how different constructs such as uncertainty avoidance, behavior intention towards social networking, trust and agent attributes will have an impact on Multi-level marketing acceptability. The research will be conducted in Nilai and the target respondents are the youth who are mostly students in the universities. Based on the literature review that was available, a framework was developed and this research was conducted through quantitative approach. The data was collected through questionnaires, analyzed using smart PLS and SPSS 20.0 software’s with multiple kinds of tests such as structural equation modeling and Mann-Whitney. The empirical findings of the study suggest that there is a strong significant difference between the Malaysia and the Arab world towards the youth willingness towards undertaking multi-level marketing as a part-time career option among the youth.